THE ROLE OF LANGUAGE AWARENESS ON GRAMMAR LEARNING IN INDONESIAN EFL CONTEXT - Andhi Dwi Nugroho; Novita Sumarlin Putri; Nur Aida Arifah (JELLT (Journal of English Language and Language Teaching), 2018)
The study aimed at investigating the affective role of integrating language  awareness  into  grammar  learning  in  the  Indonesian  EFL  (English  as  a  Foreign  Language)  context.  In the study, questionnaires and interviews on language awareness were given to fifty participants. The  findings  show that  majority  of  the  participants  responded  to  positively  change their perceptions of the relationship between learning grammar and language skills. The conclusion underlines the necessity of language awareness in grammar learning in the Indonesian EFL context as well as its future development to facilitate second/foreign language teaching and learning.